THE NEW ECONOMIC POLICY AND THE ACCOUNTING PROFESSION IN MALAYSIA: A CASE OF A MISFIT? - Azham Md. Ali (Universitas Trisakti, 2009)
Puxty et al. (1987, p. 273) argue that a concern with the social context is important if accountants are to understand their position and roles in society and if the significance of accountancy is to be assessed. In a case study format where qualitative data were gathered mainly from primary and secondary source materials and semi-structured, open-ended interviews of selected participants, the study focused on what took place in the nation's accounting arena and its immediate surrounding following the violence between Malays and Chinese in May 1969. The New Economic Policy (NEP) in 1971 changed the direction of the Malaysian economy away from a full free enterprise economy in the earlier years. As a result, the Companies Act 1965 and Accountants Act 1967 which together were aimed to facilitate the emergence of such an economy were mainly left unapplied until the mid-1980s when several important facets of the NEP were ended. In addition, the Malaysian Association of Certified Public Accountants' debilitating conduct in the field of accounting examination and training and that of promulgation/adoption of accounting/auditing standards had certainly not helped in improving the situation. All in all, accounting in Malaysia during the NEP era was in an uncertain and unsatisfactory state perhaps befitting the context it was in where the government played the main role in the nation's economy. Thus when it concerned the accounting profession and related matters in the NEP era, following Hopper et al. (1987), it can be argued that accounting development in Malaysia had been implicated in broader ideological and political struggles in the society. Keywords: Accounting, Malaysia, New Economic Policy, Malaysian Institute of Accountants, Malaysian Association of Certified Public Accountants, social context.